A rational tool for the umami evaluation of peptides based on multi-techniques. (1st March 2022) - Wang, Wenli; Yang, Luan; Ning, Menghua; Liu, Ziyuan; Liu, Yuan
Highlights: Powerful tools for screening and evaluating umami peptides were established. Evaluation tool of umami peptides based on multi-techniques is effective. Active site D in peptides reveals a further umami mechanism. D147, S276, S172 and S217 in T1R1 are the key residues combined with ligands. Abstract: Umami peptides have become of key interest in the development of flavoring agents. However, the lack of known umami peptides further prevents the understanding of the umami mechanism. The famous pufferfish ( Takifugu flavidus ) is a great resource for novel umami peptides, and we further analyze the umami characteristics of peptides based on multi-evaluation. In this study, five novel umami peptides, DF9, TK18, AK11, IK10, and GT12 were found; DF9 having the highest umami intensity, followed by AK11. Moreover, biosensor results showed DF9 with the lowest K a value of 6.85 × 10 –13 mol/L, followed by AK11. These data are mostly in agreement with sensory evaluation and fully reveal the umami mechanism of peptides. Quantum chemical and molecular docking demonstrated active site D in peptides bound with T1R1 receptor. Our results open up new strategies to estimate the taste characteristics of umami peptides and provide rational tools for screening umami peptides in food.